2012
DOI: 10.1007/s10834-012-9318-z
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Composite Measure of Green Consumption: An Exploratory Study Using a Korean Sample

Abstract: This study developed a composite measure of green consumption behaviors, incorporating multiple dimensions of green consumption behaviors. As a result of an extensive literature review, four value orientations were proposed: health-related egoistic value orientation, resourcerelated egoistic value orientation, altruistic value orientation, and biospheric value orientation. And a composite measure of green consumption which measured green consumption behavior manifesting the suggested value orientations were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 45 publications
2
54
1
4
Order By: Relevance
“…Past studies have found significant relationship between environmental concern and intention/behavior (Chan, 2001;Kim and Choi, 2005;Sinnappan and Rahman, 2011;Wahid et al, 2011). In general, marketing literature has suggested that environmental concern was associated with consumption behavior (Kim et al, 2012). Hence, we propose the following hypothesis:…”
Section: Environmental Affectmentioning
confidence: 92%
See 2 more Smart Citations
“…Past studies have found significant relationship between environmental concern and intention/behavior (Chan, 2001;Kim and Choi, 2005;Sinnappan and Rahman, 2011;Wahid et al, 2011). In general, marketing literature has suggested that environmental concern was associated with consumption behavior (Kim et al, 2012). Hence, we propose the following hypothesis:…”
Section: Environmental Affectmentioning
confidence: 92%
“…These questions were set on a 5-point scale with 1 = "strongly disagree" to 5 = "strongly agree". The second section comprised of five items measuring GCB (Kim et al, 2012). These questions were coded on 5-point scale with 1 = "least likely" to 5 = "most likely".…”
Section: Research Instruments and Data Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Kalafatis et al (1999) also suggest that extant literature provides very little information regarding the determinants of the intention to buy green products. Despite the research from numerous authors, for example Chan and Lau (2000), Cleveland et al (2005), Kim et al (2012), Laroche et al (2002), Lee (2009Lee ( , 2008 or Straughan and Roberts (1999), it is still very difficult to find a unique, consensual and reliable scale to measure GBB.…”
Section: Introductionmentioning
confidence: 99%
“…The model contemplates the linkages between values, attitudes and behaviours, as suggested by several authors (e.g. Straughan and Roberts 1999;Chan and Lau 2000;Laroche et al 2002;Cleveland et al 2005;Lee 2009Lee , 2008Kim et al 2012). …”
Section: Introductionmentioning
confidence: 99%